Perspektiven für religiöse Bildung an neuen Sekundarschulformen Eine qualitative Interviewstudie an Oberschulen und Integrierten Gesamtschulen aus religionspädagogischer Sicht - Löw, Birte (Universitätsverlag Göttingen, 2020)
The dissertation deals with perspectives on Religious Education at German comprehensive schools which were created during the 2010s. It searches for conditions and potentials of Religious Education at the referred types of school. It especially focuses on models for Religious Education as a school subject, successful activities regarding 'Religion and school life' as well as on characteristics of new comprehensive schools. It combines both questions on Religious Education as a subject and on school development. The empirical study is based on 17 interviews with teachers and school principals at so-called 'Oberschulen' and 'Integrierte Gesamtschulen', which were analyzed by qualitative content analysis. The study provides results to a neglected area of research: many studies on Religious Education or Educational Science look at grammar schools. The study creates starting points for diverse discourses and target groups. It demonstrates that Religious Education makes an important contribution to school education, but that it is time to modify some approaches and activities.